INTRODUCTION TO ALEXANDER GAVRILOV’S "HUMANISM AS ANTI-IDEOLOGY" - Adams, Hazard (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 2001)
In the context of the Third International Conference on Humanistic Discourse, this text summarizes the introduction to Alexander Gavrilov’s "Humanism as Anti-Ideology" that Hazard Adams delivered and reports on the central concerns that emerged in its discussion.